Heterogeneous catalysis by ultra-small bimetallic nanoparticles surpassing homogeneous catalysis for carbon–carbon bond forming reactions. Issue 37 (14th September 2020) - Norouzi, Nazgol; Das, Mrinmoy K.; Richard, Alexander J.; Ibrahim, Amr A.; El-Kaderi, Hani M.; El-Shall, M. Samy
Abstract : Heterogeneous Pd-based bimetallic catalysts supported on fumed silica with high activity and selectivity matching those of homogeneous catalysts have been developed for carbon–carbon cross-coupling reactions. Abstract : Palladium catalyzed cross-coupling reactions represent a significant advancement in contemporary organic synthesis as these reactions are of strategic importance in the area of pharmaceutical drug discovery and development. Supported palladium-based catalysts are highly sought-after in carbon–carbon bond forming catalytic processes to ensure catalyst recovery and reuse while preventing product contamination. This paper reports the development of heterogeneous Pd-based bimetallic catalysts supported on fumed silica that have high activity and selectivity matching those of homogeneous catalysts, eliminating the catalyst's leaching and sintering and allowing efficient recycling of the catalysts. Palladium and base metal (Cu, Ni or Co) contents of less than 1.0 wt% loading are deposited on a mesoporous fumed silica support (surface area SABET = 350 m 2 g −1 ) using strong electrostatic adsorption (SEA) yielding homogeneously alloyed nanoparticles with an average size of 1.3 nm. All bimetallic catalysts were found to be highly active toward Suzuki cross-coupling (SCC) reactions with superior activity and stability for the CuPd/SiO2 catalyst. A low CuPd/SiO2 loading (Pd: 0.3 mol%) completes the conversion of bromobenzene and phenylboronic acid to biphenyl in 30 minutes under ambient conditions in water/ethanol solvent. In contrast, monometallic Pd/SiO2 (Pd: 0.3 mol%) completes the same reaction in three hours under the same conditions. The combination of Pd with the base metals helps in retaining the Pd 0 status by charge donation from the base metals to Pd, thus lowering the activation energy of the aryl halide oxidative addition step. Along with its exceptional activity, CuPd/SiO2 exhibits excellent recycling performance with a turnover frequency (TOF) of 280 000 h −1 under microwave reaction conditions at 60 °C. Our study demonstrates that SEA is an excellent synthetic strategy for depositing ultra-small Pd-based bimetallic nanoparticles on porous silica for SCC. This avenue not only provides highly active and sintering-resistant catalysts but also significantly lowers Pd contents in the catalysts without compromising catalytic activity, making the catalysts very practical for large-scale applications.